Deconstructing the Male Gaze: Digital Short Films as an Alternative Space for Gender Representation - Deddy Suprapto; Aris Saefulloh; Rara Mustika Ningrum; Lilik Kustanto; Ahmad Jufriyadi (Faculty of Humanities, Universitas Jenderal Soedirman, 2026)
This study analyzes how Indonesian short films, particularly Demi Nama Baik Kampus (2021), challenge the dominance of the male gaze and present more critical and inclusive representations of gender. While previous studies on the male gaze in Indonesian cinema have primarily focused on mainstream feature films and representations of women as objects of patriarchal narratives, limited attention has been given to digital short films as alternative spaces for resisting gendered visual regimes. This study addresses this gap by examining how a digitally distributed short film constructs resistance to the male gaze across textual, discursive, and socio-cultural dimensions. Using Norman Fairclough's (1995) Critical Discourse Analysis (CDA) approach, this study examines three levels of analysis: text, discourse practice, and socio-cultural practice. At the text level, the study reveals how the film's dialogue, visual symbols, and narrative deconstruct the objectification of women by presenting a protagonist who actively fights against sexual violence on campus. At the discourse practice level, YouTube expands access to gender issues and challenges conventional distribution and censorship practices. At the socio-cultural practice level, the study links the film's representation to the context of campus patriarchy, state regulations related to sexual violence, and the dynamics of digital capitalism that shape the visibility patterns of short films. The results of the study show at least six forms of resistance to the male gaze displayed through the character of Sinta: rejection of sexual objectification, resistance to threats, rejection of institutional intimidation, reporting to the PPKS (Pencegahan dan Penanganan Kekerasan Seksual) Task Force, public disclosure of cases, and solidarity among women. These findings confirm that digital short films in Indonesia can serve as an alternative medium for deconstructing patriarchal discourse and expanding the audience's critical awareness of gender relations in the digital age.